PENGARUH TRADING VOLUME ACTIVITY (TVA), RETURN ON ASSET (ROA), DAN DEVIDEN PER RATIO (DPR) TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2022 - Fernandho Rudy Husin; Usnia Wati Keristin (Universitas Multi Data Palembang, 2025)
The purpose of this study is to analyze the influence or relationship of Trading Volume Activity (TVA), Return on Assets (ROA), and Dividend Payout Ratio (DPR) on the stock prices of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The method used in this study is a quantitative approach with secondary data obtained from annual reports published by publicly traded mining companies. In this study, the company sample was obtained using a purposive sampling method. The analytical techniques used to analyze the data in this study include descriptive statistical tests, classical assumption tests such as normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests, and hypothesis tests, namely partial and simultaneous tests. This study shows that TVA and ROA have a significant partial influence on stock prices, while DPR has no significant influence on stock prices. Simultaneously, TVA, ROA, and DPR have a significant influence on stock prices of mining companies.